2017
DOI: 10.1093/ckj/sfw151
|View full text |Cite
|
Sign up to set email alerts
|

Time, timing, talking and training: findings from an exploratory action research study to improve quality of end of life care for minority ethnic kidney patients

Abstract: Background. With an ageing and increasingly diverse population at risk from rising levels of obesity, diabetes and cardiovascular disease, including kidney complications, there is a need to provide quality care at all stages in the care pathway including at the end of life and to all patients. Aim. This study purposively explored South Asian patients’ experiences of kidney end of life care to understand how services can be delivered in a way that meets diverse patient needs. Methods. Within an action research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Nineteen studies identified the issue of communication between South Asian migrant patients/families and their HPs in PC (Ackroyd, 2003; Biondo et al, 2017; Doorenbos, 2003; Khosla et al, 2016; Khosla et al, 2017; Owens and Randhawa, 2004; Radhakrishnan et al, 2017; Randhawa and Owens, 2004; Randhawa et al, 2003; Shanmugasundaram and O'Connor, 2009; Sharma et al, 2012; Somerville, 2001; Venkatasalu et al, 2013; Weerasinghe and Maddalena, 2016; Wilkinson et al, 2016; Wilkinson, Randhawa, et al, 2017; Wilkinson et al, 2014; Wilkinson, Waqar, et al, 2017; Worth et al, 2009). Communication was identified as the key and most crucial factor in access to PC (Randhawa and Owens, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen studies identified the issue of communication between South Asian migrant patients/families and their HPs in PC (Ackroyd, 2003; Biondo et al, 2017; Doorenbos, 2003; Khosla et al, 2016; Khosla et al, 2017; Owens and Randhawa, 2004; Radhakrishnan et al, 2017; Randhawa and Owens, 2004; Randhawa et al, 2003; Shanmugasundaram and O'Connor, 2009; Sharma et al, 2012; Somerville, 2001; Venkatasalu et al, 2013; Weerasinghe and Maddalena, 2016; Wilkinson et al, 2016; Wilkinson, Randhawa, et al, 2017; Wilkinson et al, 2014; Wilkinson, Waqar, et al, 2017; Worth et al, 2009). Communication was identified as the key and most crucial factor in access to PC (Randhawa and Owens, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, relatives with knowledge of health-related issues could work as mediators between HPs and other family members (Weerasinghe and Maddalena, 2016). Although involving relatives facilitated communication between HPs and family members (Wilkinson, Randhawa, et al, 2017), communication barriers also existed within the patients’ family (Somerville, 2001). Relatives found it difficult to communicate the poor prognosis of the patient to other family members who knew less about the trajectory as a whole (Somerville, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence from the peer-reviewed literature indicated that patient experience data were often captured from individuals or families whilst in a clinical setting. In 49 studies, PREMs were captured while individuals were visiting, being admitted to, or discharged from, hospitals [ 14 17 , 21 , 23 , 25 , 29 , 31 , 33 , 36 , 37 , 44 , 49 , 51 , 52 , 54 , 60 , 62 , 63 , 65 , 68 , 73 , 76 , 81 , 82 , 94 96 ] or while individuals were visiting primary care clinics [ 18 20 , 26 , 30 , 38 , 42 , 43 , 54 , 58 , 59 , 69 , 70 , 75 , 78 , 97 102 ]. Thirty-one further studies reported PREMs being gathered via community and/or online environments.…”
Section: Resultsmentioning
confidence: 99%